Single-cell transcriptome sequencing reveals potential novel combination of biomarkers for antibody-based cancer therapeutics in hepatocellular carcinoma - Tang, Hong; Yuan, Jun; Gong, Yuan-Feng; Zhang, Cheng-Yang; Liu, Ming; Luo, Su-Xia (Frontiers in Genetics, 2022)
Background: Antibody-based Cancer therapeutics are developing rapidly in recent years for its advantages in precisely targeting the tumor cells. However, tumor-specific cell surface antigens are still lacking, and the heterogeneity of tumor mass greatly impeded the development of effective drugs. Methods: In the present study, single-cell RNA sequencing was used to dissect tumor heterogeneity in human hepatocellular carcinoma (HCC). Tissues from different spatial regions including the tumor, para-tumor, and distant normal liver tissues were dissociated into single cells and the gene expressions were compared in different subpopulation of cells from these regions and validated in independent cohorts. Results: A total of 28 cell clusters with different distribution pattern and gene expression profile was identified within a heterogenous tumor and its paired liver tissues. Differentially expressed genes encoding plasma membrane in cells with hepatic lineage were further extracted from single-cell transcriptome sequencing and validated in TCGA database. A 3-gene signature was identified to be significantly up-regulated in dominant HCC tumor cell subpopulations with prognostic significance and validated in multiple independent patient cohorts. Conclusions: The composition of the three plasma membrane proteins on the surface of HCC tumor cells within a heterogenous tumor might indicate poor prognostic tumor subpopulations during cancer evolution and potential therapeutic targets.